Radioactive label polypeptide coordination complex and preparation method and application thereof - ZHANG XIANZHONG; LIU GANG; LANG LIXIN; LUO SHINENG; YANG MIN; PAN DONGHUI; CHEN XIAOYUAN (2013)
The invention provides an RGD polypeptide coordination complex of a radioactive nuclide label. According to the structure of the coordination complex, the radioactive nuclide is selected from 64Cu, 68Ga, 111In, 62Cu, 67Cu, 67Ga, 86Y, 89Zr or 18F; the ligand is a ligand compound containing an RGD structure, which is shown in a formula (I). The coordination complex has stronger ligand stability and high target/non-target ratio, and the appetency of the ligand with integrin AlphavBeta3 is stronger. The invention further provides a preparation method of the coordination complex, and an application of the coordination complex in preparing tumor developers.